Розвиток галузевих ринків в умовах глобалізації - Яковенко, Р. В.; Yakovenko, R.; Щельник, О. В.; Schelnyk, O. (Кіровоград : видавець Лисенко В. Ф., 2015)
Стаття розкриває основні чинники формування, функціонування та розвитку галузевих ринків країн світу в умовах глобалізації. The article reveals the main factors of the formation, functioning and development of the branch markets of the world in the conditions of globalization.
Development of branch markets in the conditions of globalization
Keywords: глобалізація; інформаційна економіка; економічний розвиток; сектор економіки; теорія промислової організації; globalization; informational economy; economic development; sector of economy; theory of industrial organization